Implications of decentralisation for disaster governance in Nepal’s federalism: Case study of COVID-19 response of four selected local governments - Pokharel, Kushal; Devkota, Kamal; Fischer, Harry; Khatri, Dil; Maskey, Gyanu (New Angle: Nepal Journal of Social Science and Public Policy, 2023)
Nepal’s entry into federalism in 2015 resulted in a decentralised governance structure with constitutionally mandated legislative, executive and judicial functions for local governments. Existing research shows that devolving discretionary authority and resources to local governments is a necessary but not a sufficient condition for effective local responses during crises. However, there remains a need for deeper understanding about what makes local governments effective in responding to people’s needs during crisis times. Adopting a qualitative approach, this research analyses how decentralisation shapes local government responses in times of distress. We ask: How did local governments in Nepal respond to urgent needs during the COVID-19 pandemic – and what has been learned from this crisis that can make local governments better prepared for future challenges? Findings of this study show that the effective governance response to the crisis depends on several factors such as existing infrastructure development, availability of human and financial resources, political connections of local leadership, and local leaders’ ability to envision and execute the plans in a highly uncertain and quickly developing situation. The local government’s response to COVID-19 in Nepal shows the important role of decentralised local governance in combating crises, but there remain several critical challenges to make local governments more effective. In particular, we argue that it is essential to ensure sustained access to financial resources, strengthen human resource capabilities through training and capacity building activities, and prepare local governments to deliver important services in the context of disaster situations.